Structure and ferroelectric behaviour of Na0.5Bi0.5TiO3-KNbO3 ceramics. (17th February 2016) - Wang, G.; Hall, D. A.; Comyn, T. P.; Daniel, L.; Kleppe, A. K.
Abstract : Lead-free piezoelectric ceramics, (1− x )Na0.5 Bi0.5 TiO3 - x KNbO3 (NBT- x KN), with x = 0.02–0.08 were fabricated by solid-state reaction and sintering. The crystal structures and dielectric properties were measured for different KN contents. All compositions in the unpoled, as-sintered state were found to be single-phase pseudo-cubic. However, typical ferroelectric behaviour, with well-saturated polarisation-electric field hysteresis loops, was observed for certain compositions at high electric field levels. It is shown using high-energy synchrotron X-ray diffraction that the application of the electric field induced an irreversible structural transformation from the nano-polar pseudo-cubic phase to a ferroelectric rhombohedral phase. The changes in lattice elastic strain and crystallographic texture of a poled NBT-0.02KN specimen as a function of the grain orientation, ψ, conform well to those expected for a conventional rhombohedrally distorted perovskite ferroelectric ceramic. The dielectric permittivity-temperature relationships for all compositions exhibit two transition temperatures and a frequency-dependent behaviour that is typical of a relaxor ferroelectric. The transition temperatures and grain size decrease with the increasing KN content.